Characteristic Polynomial and Eigenproblem of Triangular Matrix over Interval Min-Plus Algebra - Rahmawati, Anita Dwi; Siswanto, Siswanto; Wibowo, Supriyadi (Universitas Muhammadiyah Mataram, 2024)
A min-plus algebra is a linear algebra over the semiring R_ε', equipped with the operations “